First Complete Mitochondrial Genome of Nigropunctata complanata—A New Record for China - Li, Wen-Hao; Habib, Kamran; Yao, Zu-Quan; Wang, Guo-Yu; Wang, Xian-Yi; Li, Qi-Rui; Kang, Ji-Chuan (Phytotaxa, 2026)
In the present study, the high-quality whole-genome of Nigropunctata complanata strain (GMB4912) was sequenced on the MGI-T7 sequencing platform. Species identification was confirmed via comprehensive morphological assessment and multi-locus phylogenetic analysis using ITS, LSU, rpb2, tef1-α and tub2 sequences. The circular mitogenome spans 45,779 base pairs (bp), encoding 43 genes, including 15 protein-coding genes (14 respiratory chain subunits and the ribosomal protein gene rps3), 26 tRNA genes, and 2 rRNA genes. Mitogenome-based phylogenetic analysis confirmed its placement within the order Xylariales with high support (BS=96%). This represents the first complete mitochondrial genome for both the genus Nigropunctata and the family Pallidoperidiaceae. The data provides a valuable genomic resource for future studies on fungal taxonomy, phylogenetics, and species boundaries within Xylariales.